Multiple variables influence the finely calibrated antioxidant defenses of Clostridioides difficile - Erin B. Purcell (mBio)
ABSTRACT The obligate anaerobe Clostridioides difficile encodes multiple reductases to detoxify molecular oxygen and reactive oxygen species. Caulat and colleagues have characterized the activity and regulation of four such reductases (L. C. Caulat, A. Lotoux, M. C. Martins, N. Kint, et al., mBio 15:e01591-24, 2024, https://doi.org/10.1128/mbio.01591-24). Each proved critical for clostridial survival in a different range of oxygen concentrations; together, they ameliorate a broad range of oxidative stress levels. Moreover, two previously uncharacterized regulators were found to control reductase gene expression in response to oxidative stress. The genetic repressor Rex and the reductase FdpF are both sensitive to the NAP+:NADH ratio, which is affected by a cell’s metabolic state as well as redox activity. While oxygen is known to influence the expression of metabolism genes in C. difficile, the mechanisms for cross-talk between the pathways that respond to oxidative and metabolic stress are not well known. The NADH dependence of Rex and FdpF may represent a newly mapped junction between these pathways.